Scientific values of ECA Ligation - Jachmen Sultana; Abul Bashar; Sobhan Morol (New Horizons in Medicine and Medical Research Vol. 8, 2022)
Ligation of the carotid artery was formerly used as an emergency technique to control massive haemorrhages in the head and neck region. Though it was discarded due to the high mortality and morbidity of patients. But over the succeeding decades, a more selective branch of the carotid artery that is ECA ligation have been popularized for the same purpose due to lack of or minor postsurgical complications compared to Transarterial embolization (TAE). However, sometimes a good surge seal pack especially in the maxilla is necessary to control both the collateral circulation and backflow of blood distal to carotid from the internal carotid arteries (ICA). Nonetheless, ECA ligation would be a better option to control life-threatening uncontrolled bleeding in this region.